(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
The aim of this study was to determine the role of occupation-related physical activities in the osteoarthritis of the knee. The study was conducted on 87 female patients from September 2016 to August 2017. The same number of healthy females of the same age group were included as a control. Data was collected using a structured interviewer-administered questionnaire, enquiring about demographic data and details of risk factors. There were statistically significant (p<0.05) changes in the occupation-related physical activities like sustained knee bending, climbing stairs (>10 flights/day), kneeling (>30 min/day), squatting (>30 min/day), in patients when compared to the control group. However, there were no significant changes in other occupation-related physical activities. Obese (BMI ≥30 kg/m2) patients were found 29.9% in the patient and 17.2% in the control group. Patients with a positive family history of osteoarthritis of the knee were 13.8% in the case group and 3.4% in the control group. The difference was statistically significant (p<0.05) between the two groups. In conclusion, occupation-related physical activities like sustained knee bending, climbing stairs, kneeling and squatting had a significant association with osteoarthritis of the knee in the female.